Identification of Alzheimer Disease: A Literature Survey - Natarajan, M.; Sathiamoorthy, S. (Asian Journal of Electrical Sciences, 2018)
Medical imaging works an essential part in the area of medical science. In today scenario, image segmentation is utilized to extricate abnormal tissues from normal tissues directly in medical images. Noise in an image is unacceptable to us as it interrupts and deteriorates the condition of the image. Noise removal is perpetually a challenging responsibility so as of edge protection when the strength of the disturbing noise in the initial image is enormous. Alzheimer’s disease is a neurological dysfunction in which the brain death causes cognitive decline and Memory Loss. A neurodegenerative kind of dementia, the condition begins with mild and grows increasingly severe. A crucial area of medical research is Brain image examination, ends to identify brain diseases. The leading causes of Alzheimer’s diseases are Moderate blood flow and brain activity. In this paper, a framework has introduced for the exposure of Alzheimer disease and a literature survey on Image Processing for the AD. This framework optimally determines the Alzheimer field in the neurological disorder.